Cryopreservation of dammar (Agathis damara Salisb.) seeds in liquid nitrogen - DHARMAWATI FERRY DJAM’AN; DODY PRIADI; ENNY SUDARMANOWATI (Biodiversitas Journal of Biological Diversity, 2006)
Dammar (Agathis damara) seeds categorized as an intermediate seeds since their viability tend to decrease when subjected to storage more than 2 weeks conventionally. Storage period of seeds could be prolonged when the seeds cryopreserved in liquid nitrogen since the metabolism of the cells could be minimized without loss of viability. The objective of the study was to identify suitable vitritification method for dammar storage seeds. Seed water content was decreased gradually from initial water content (28.48% as a control) using desiccators and vacuum method. Vitrification solution (PVS2) containing glycerol 30%, ethylene glycol 15% and dimethylsulfoxide (DMSO) 15% in 0.4M sucrose solution was used as a cryoprotectant of peeled or unpeeled dammar seeds during freezing process. The samples were soaked in PVS2 for 1 hour followed by exposure to liquid nitrogen in cryotube for 1 hour. The samples were then thawed in water bath at 28°C for 1 hour prior to germination in IPB-78 germinator with UDK and UKdDp germination methods. Results showed that the highest viability of cryopreserved dammar seeds (22.32% moisture content) was 100% obtained from those germinated with UKdDp method. A negative effect of cryoprotectant was occurred in both peeled and unpeeled seeds cryopreserved for 1 hour. However, it was effective for seeds cryopreserved for 4 weeks which indicate the possibility to preserve for a longer period in the future. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: dammar, Agathis damara, seeds, PVS2, crypreservation.